EFEKTIFITAS PEMBERIAN SUSU KAMBING FERMENTASI TERHADAP ANTROPOMETRI BAYI BARU LAHIR - Ira Suryanis; Hasmiwati, Hasmiwati; Nur Indrawaty Lipoeto; Novirman Jamarun (Nusantara Hasana Journal, 2025)
The balance of the gut microbiota during pregnancy is essential for maintaining maternal health and supporting optimal fetal development. Fermented goat’s milk contains naturally occurring probiotics that contribute to microbiota homeostasis and improved maternal nutritional status. This study aimed to evaluate the effect of fermented goat’s milk consumption on newborn anthropometric outcomes. Two group pretest posttest control was applied involving 15 third-trimester pregnant women who met the inclusion criteria. Participants consumed 75 mL of fermented goat’s milk daily for a period of 9–12 weeks. Maternal characteristics and neonatal anthropometric parameters were collected through structured observations and questionnaires. Data were analyzed using paired statistical tests. The findings demonstrated statistically significant improvements (p < 0.05) in neonatal birth weight, body length, and head circumference following the intervention. These results indicate that fermented goat’s milk may positively influence fetal growth without inducing gut microbiota dysbiosis. Further studies employing controlled designs and larger sample sizes are warranted to confirm these findings and elucidate the underlying mechanisms.